Structural Optimization Design of Automobile Windshield Heating Furnace Based on Workbench - Anheng Wang; Tao Wang; Chuanwen Ling; Hui Wang; Xiang Zhao; Wentao Zhu (Engineering Reports, 2025)
ABSTRACT This article optimizes the structural optimization of the high‐temperature heating furnace used in the front glass manufacturing process of automobiles. In order to improve the heat condition in the glass forming process, the steady‐state thermal module of the finite element analysis software ANSYS Workbench is used to simulate the thermal forming process of the automotive front gear glass, and the influence of the specific heat of the front gear glass at rising temperature, the coefficient of thermal expansion, the coefficient of radiation heat transfer, and other parameters on the forming accuracy are studied. The mechanical properties and viscosity curve of the front glass were analyzed with the change of temperature, the collaborative service integration of “preheating‐injection molding‐pressing‐gluing” of the front glass was established, the thermoforming process was optimized, the temperature–force field thermodynamic coupling model was created, and the reliability of the constitutive model and simulation of the front glass was verified. It makes up for the deficiency that the existing theoretical research is separated from the actual generation and cannot play an effective guide to the production practice. This paper provides a new scheme for the structure design of automotive front gear glass heating furnace and provides reference for other similar forming structures.